Alteration of N6-Methyladenosine RNA Profiles in Cisplatin-Induced Acute Kidney Injury in Mice - Li, Can-Ming; Li, Ming; Zhao, Wen-Bo; Ye, Zeng-Chun; Peng, Hui (Frontiers in Molecular Biosciences, 2021)
Aim: To identify the alterations of N6-methyladenosine (m6A) RNA profiles in cisplatin-induced acute kidney injury (Cis-AKI) in mice. Materials & methods: The total level of m6A and the expression of methyltransferases and demethylases in kidneys were measured. The profiles of methylated RNAs were determined by the microarray method. Bioinformatics analysis was performed to predict the functions. Results: Global m6A levels were increased after cisplatin treatment, accompanied by the alterations of Mettl3, Mettl14, Wtap, Fto, and Alkbh5. A total of 618 mRNAs and 98 lncRNAs were significantly differentially methylated in response to cisplatin treatment. Bioinformatics analysis indicated that the methylated mRNAs predominantly acted on metabolic process. Conclusion: M6A epitranscriptome might be significantly altered in Cis-AKI, which is potentially implicated in the development of nephrotoxicity.